A childhood acute lymphoblastic leukemia (ALL) case with t(3;17)(q23;p13),t(5;12)(q31;p13),inv(11)(p15q12) - (:unkn) unknown (My University, 2008)
It is known that clonal chromosomal changes in childhood ALL are nonrandom and important markers for diagnosis, prognosis and relaps. In this report we present 4 year-old boy with ALL-L1 who has complex chromosomal rearrangements. Chromosome analysis was performed on bone marrow aspiration sample in relaps after one year from diagnosis and induction chemotherapy. The karyotype was; 46,XY,t(3;17)(q23;p13),t(5;12)(q31;p13),inv(11)(p15q12) [11]/46,XY[8] (Turk J Hematol 2006, 25: 152-4).
Keywords: All; Chromosome aberrations; Cytogenetics; Translocation